Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Rapid detection of LMBV using rabbit-derived single-chain antibodies via fluorescent immunochromatography assay - Zhou Chen; Jun-Yao Xia; Tian-Zi Sun; Mao-Lin Liu; Jia-Lun Tang; Zhao Zhao; Bin Zhu (Aquaculture, 2027)

Engineering Chlorella-based consortia for sustainable food wastewater treatment: nutrient recovery, pollutant degradation and advanced harvesting - Lin Zhao; Shujie Wei; Yifan Zhang; Luguang Tao; Yuwei Xu; Yiming Wang; Zhangli Hu; Jun Tang; Song Wang (Environmental Research, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Lanthanum-modified biochar for dual removal of particulate/dissolved phosphorus in agricultural runoff: Performance and reuse as slow-release fertilizer - Ting Chen; Jiayi Lu; Fenghao Lin; Zhiqiang Chen; Junjie Wei; Jie He; Ying Wang; Xiujuan Tang; Jun Yin (Journal of Environmental Sciences, 2026)

Syn-tectonic emplacement of Li-bearing pegmatites related to detachment faulting in the Dahongliutan pegmatite belt, Western Kunlun, NW China - Tao Hong; Matthieu Harlaux; Ming-Guo Zhai; Yue-Jun Wang; Xing-Wang Xu; Xiao-Ping Xia; Jun Gao; Jun-Lin Tang; Ming-Xi Hu; Huan-Xiang Gao (Mineralium Deposita, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Formation of dichloroacetonitrile and halonitromethanes from Pseudomonas aeruginosa during UV265-LED/chlorine disinfection - Qian Tang; Lin Deng; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Hazardous Materials, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Mechanistic insights into the effects of roasting on heat-induced hazard formation and lipid oxidation stability in camellia seeds - Tongqiang Chen; Xiaojuan Wu; Jun Xiang; Helin Li; Kailong Li; Haizhi Wu; Wenjie Tang; Can Li; Qinlu Lin; Wei Wu (Food Chemistry, 2026)

A bipolar membrane-driven proton self-supply strategy for the sustained and efficient electrosynthesis of Na2S2O4 from desulfurization byproduct - Yingxue Fu; Jun Wu; Hao Chen; Lin Wu; Zhujiang Wang; Yelin Zhu; Jiaqi Long; Zhipeng Tang; Fenghua Shen; Kaisong Xiang; Hui Liu (Chemical Engineering Journal, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Insights into the formation of dichloroacetonitrile and halonitromethanes from Escherichia coli during UV-LED (265 nm)/chlorine disinfection - Qian Tang; Lin Deng; Tao Wang; Chaoqun Tan; Changbo Zhang; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2026)

Corrigendum to “Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms” [J. Environ. Chem. Eng., 13:5 (2025) 119015] - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2026)

Achieving long-life high-voltage Ni-rich cathodes by mitigating lattice and grain-boundary degradation - Jun Chen; Haoji Wang; Junguang Sun; Zebo Gu; Junyong Deng; Guorong Liu; Kun Huang; Siyao Zhang; Hao Feng; Wentao Wang; Hao Chen; Xinya Tang; et al. (Chemical Engineering Journal, 2026)

The Biological Effects of Boron in Animals and Humans - Changlin Hong; Xin Chen; Jiaruo Tang; Jun Chen; Yanan Xue; Jiayu Zhang; Xiao Lin (Biological Trace Element Research, 2026)

A global intercomparison of SWOT and traditional nadir radar altimetry for monitoring river water surface elevation - Yue Xu; Frédéric Frappart; Guoqiang Tang; Guoqing Zhang; Peirong Lin; Liguang Jiang; Simon Papalexiou; Fangfang Yao; Xiaoran Han; Jun Xia (Remote Sensing of Environment, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Coal tar phenolic DES back-extraction study based on Hansen parameters: A combined experimental and computational approach - Dezhi Cao; Dingkai Hu; Wenna Wang; Xinyue Lin; Xinpeng Bi; Jun Tang; Qiang Wang (Fuel, 2026)

Soil calcium ion enrichment associated with altered microbial functional gene networks in bamboo forest expansion - Yaoxing Wu; Huimin Tian; Jiahuan Guo; Yawen Shen; Qingqing Liu; Lin Yu; Zhiyin Tang; Yihang Jia; Gong Zhang; Jun Deng; Lianghua Qi (Applied Soil Ecology, 2026)

Assessment of provincial PV recycling potential: Integrating product lifetime distribution and scrap capacity - Bao-Jun Tang; Wen Shi; Ru Li; Xi-Lin Cao (Sustainable Production and Consumption, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

A DESN-based federated learning framework for NIR spectral analysis of organic carbon in farmland soils - Huazhou Chen; Jun Xie; Bin Lin; Lili Xu; Fangxiu Meng; Guoqiang Tang (Computers and Electronics in Agriculture, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Geophysical monitoring technology and simulation in CO2 geological storage: A comprehensive review - Wenke Tang; Wuqin Li; Zitian Lin; Jun Zhu; Siyao Zhou; Yangmin Kuang; Yanpeng Zheng (Gas Science and Engineering, 2025)

Rapid inactivation of Bacillus cereus and formation of bacterial-derived nitrogenous disinfection byproducts during UV265-LED/chlorine disinfection - Qian Tang; Lin Deng; Tao Wang; Chaoqun Tan; Changbo Zhang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Chemical Engineering, 2025)

Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Subclinical atrial fibrillation prediction based on deep learning and strain analysis using echocardiography - Sung-Hao Huang; Ying-Chi Lin; Ling Chen; Sayan Unankard; Vincent S. Tseng; Hsuan-Ming Tsao; Gau-Jun Tang (Medical & Biological Engineering & Computing, 2025)
Subclinical atrial fibrillation (SCAF), also known as atrial high-rate episodes (AHREs), refers to asymptomatic heart rate elevations associated with increased risks of atrial fibrillation and cardiovascular events. Although deep learning (DL) models leveraging echocardiographic images from ultrasound are widely used for cardiac function analysis, their application to AHRE prediction remains unexplored. This study introduces a novel DL-based framework for automatic AHRE detection using echocardiograms. The approach encompasses left atrium (LA) segmentation, LA strain feature extraction, and AHRE classification. Data from 117 patients with cardiac implantable electronic devices undergoing echocardiography were analyzed, with 80% allocated to the development set and 20% to the test set. LA segmentation accuracy was quantified using the Dice coefficient, yielding scores of 0.923 for the LA cavity and 0.741 for the LA wall. For AHRE classification, metrics such as area under the curve (AUC), accuracy, sensitivity, and specificity were employed. A transformer-based model integrating patient characteristics demonstrated robust performance, achieving mean AUC of 0.815, accuracy of 0.809, sensitivity of 0.800, and specificity of 0.783 for a 24-h AHRE duration threshold. This framework represents a reliable tool for AHRE assessment and holds significant potential for early SCAF detection, enhancing clinical decision-making and patient outcomes. Graphical abstract

A precisely regulated Streptomyces expression system pTZYp facilitated by the strong promoter stnY and cmt operon - Kai Zhang; Ao-yu Wang; Qiang Zhou; Yi-feng Chen; Shuang-jun Lin; Gong-li Tang (Biotechnology Letters, 2025)

The molecular mechanisms and therapeutic implications of PANoptosis in ischemic diseases - Jiangpeng Wu; Xunkai Wang; Jin Peng; Jinxi Liang; Jun Lv; Lin Huang; Shenmei Wu; Chen Yao; Guiyun Jin; Tang Deng (Apoptosis, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Amino-functionalized MIL-101(Fe)-NH2 as efficient peracetic acid activator for selective contaminant degradation: Unraveling the role of electron-donating ligands in Fe(IV) generation - Renjie Pan; Zongchen Li; Tian-Yang Zhang; Qi Fu; Zheng-Xiong Zheng; Jun Shi; Jian Lu; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Journal of Hazardous Materials, 2025)

Application of multi-electron donor autotrophic denitrification (MEDAD) substrate in constructed wetlands for treating low carbon-to‑nitrogen ratio wastewater: A feasible framework - Lin Zhao; Yifan Zhang; Jun Tang (Ecological Engineering, 2025)

Study on dynamic changes in characteristic volatile compounds uncovers aroma development of Hainan Dayezhong (Camellia sinensis var. assamica) black tea - Yunfei Hu; Jialin Wang; Jun Tang; Ronghua Huang; Wenyuan Luo; Yanming Tuo; Ningkai Liao; Dawen Zhuang; Jinke Lin; Yue Zhang; Lei Pan; Liangyu Wu (Food Chemistry, 2025)

Urea-crosslinked 3D graphene oxide/MXene-SO3/cyclodextrin films for efficient and sustainable biodiesel production - Qi Ao; Lin Jiang; Jun Tang (Carbohydrate Polymers, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Characteristics of Impact Fragmentation and Energy Dissipation of Cylindrical Rock Specimens with Various Aspect Ratios - Yuzhong Qin; Lin Lang; Shuang Tian; Tong Wu; Huaizi Tang; Jun Xu; Yingda Zhang; Jingmei Wang; Huijun Lu; Zheming Zhu (Rock Mechanics and Rock Engineering, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Luminescence dating of core DLC70-2 from the North Yellow Sea in China and its implication for late Quaternary transgressions - Nan Tang; Zhongbo Wang; Penghui Lin; Yuexin Liu; Zonghui Wu; Haozheng Tian; Xi Mei; Jun Sun; Jianghao Qi; Rihui Li; Shuyu Wu; Hongxian Chu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of bromide ion on the formation and toxicity of halonitromethanes from Microcystis aeruginosa solution during UV/chloramine disinfection - Qi Xue; Qian Tang; Lin Deng; Wei Luo; Mingle Xia; Shuang Fu; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2025)

Formation of halonitromethanes, dichloroacetonitrile, and trichloromethane in the presence of E. coli and nitrophenols during UV/post-chlorination - Tao Wang; Qian Tang; Lin Deng; Chaoqun Tan; Yulin Fu; Jun Hu; Rajendra Prasad Singh (Journal of Hazardous Materials, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Construction of 3D MXene-SO3/graphene oxide/cyclodextrin heterogeneous hybrid aerogels for green and efficient catalysis production of ethyl acetate - Qi Ao; Xiaoxiao Lv; Lin Jiang; Jun Tang (Chemical Engineering Journal, 2025)

Efficiently radiation-induced degradation and extraction of Polygonatum sibiricum polysaccharides and its excellent ROS scavenging properties - Dong-Xu Tang; Shi-Zhong Zhou; Zhi-Jun Wang; Yang-Lin Zhang; Kun Liu; Jin-Yu Yang; Xiao-Jie Yang; Yue-Sheng Li; Xia Zhang (Chemical Engineering Journal, 2025)

Deciphering the inhibitory mechanisms of didecyldimethylammonium chloride on microalgal removal of fluoxetine: Insights from the alterations in cell surface properties and the physio-biochemical and molecular toxicity - Zhengxin Xie; Lin Pan; Meng Nie; Guiyuan Cai; Hebin Liang; Jun Tang; Xiaoli Zhao (Science of The Total Environment, 2025)

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

Echelon extraction of valuable components from salt lake brine substrate - Xiangting Tang; Jun Chen; Ye Zhang; Jianguo Yu; Sen Lin (Desalination, 2025)

Coexistence of B. cereus and nitrophenols affecting the formation of chlorinated halonitromethanes, dichloroacetonitrile, and trichloromethane during the sequential UV-chlorine disinfection process - Tao Wang; Qian Tang; Lin Deng; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Chemical Engineering Journal, 2025)

Probing into the formation of brominated halonitromethanes from the intracellular organic matter of Anabaena during UV/chlorine disinfection - Aoxiang Cao; Qian Tang; Lin Deng; Yanyu Xu; Qi Xue; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Chemical Engineering, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Study on metabolic variation reveals metabolites important for flavor development and antioxidant property of Hainan Dayezhong black tea - Yunfei Hu; Jialin Wang; Wenyuan Luo; Jun Tang; Yanming Tuo; Ningkai Liao; Dawen Zhuang; Kehang Yang; Jinke Lin; Yue Zhang; Liangyu Wu (Food Research International, 2024)

Chemical leaching − Flexible precipitation for sustainable recovery of fluoride from aluminum electrolysis multisource hazardous waste - Lutong Ma; Zhesheng Qiu; Yusheng Tang; Wanzhang Yang; Bensong Chen; Jun Jiang; Yan Lin (Chemical Engineering Journal, 2024)

Base on photothermal interfacial molecular transfer for efficient biodiesel catalysis via enzyme@cyclodextrin metal-organic frameworks loaded MXene - Qi Ao; Lin Jiang; Ying Song; Xinglai Tong; Tuohao Jiang; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2024)

OSL and radiocarbon dating of core TBF-1 on the outer shelf of the East China Sea and implications for late Quaternary stratigraphic correlation - Zhongbo Wang; Nan Tang; Penghui Lin; Pengyu Qiao; Kai Lu; Xi Mei; Jun Sun; Jianghao Qi; Yang Wang; Hongxian Chu; Zhongping Lai (Quaternary Geochronology, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Experimental investigation on the horizontal impact response of precast RC bridge piers with grouted sleeve connections considering defects - An He; Dun-Cong Zheng; Jian Cai; Qing-Jun Chen; Xu-Lin Tang; Jia-Bin Ye (Engineering Structures, 2024)

Overlooked role of protocatechuic acid in enhancing the selective elimination of sulfonamide antibiotics in Fe(III)/peroxymonosulfate process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Zhijie Wu; Chenyu Tang; Linfeng He; Xiaobin Liao; Jun Ma (Chemical Engineering Journal, 2024)

A nanoenzyme reactor fueled by a High-Glucose microenvironment for augmented diabetic tumor therapy - Zhi-Chao Hu; Hong-Jun Zhuang; Li-Yi Zhang; Qian Tang; Zhe Liu; Zi-Hao Lin; Ruo-Tao Liu; Zi-Yi Wang; Xiao-Hui Chen; Zhen-Zhong Zhu; Tao Yi; Li-Bo Jiang (Chemical Engineering Journal, 2024)

The recycling of carbon-rich solid wastes from aluminum electrolytic cells: a review - Lutong Ma; Zhesheng Qiu; Yusheng Tang; Wanzhang Yang; Bensong Chen; Jun Jiang; Yan Lin (Environmental Chemistry Letters, 2024)

Analysis of the Spatio-Temporal Characteristics of Winter Surface Urban Heat Island: A Case Study in Beijing, China - Shanshan Lu; Fujiang Liu; Yunshuang Ye; Jiayu Tang; Peng Li; Weihua Lin; Yan Guo; Ruqiang Ma; Jun Wang (Journal of Earth Science, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Dual-carbon isotope analysis of benzene polycarboxylic acids for tracking black carbon across different environments - Xin Yi; Guangcai Zhong; Xiaofei Geng; Jiao Tang; Boji Lin; Sanyuan Zhu; Shutao Gao; Chuxin Yao; Zhineng Cheng; Shizhen Zhao; Jun Li; Gan Zhang (Applied Geochemistry, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

Assessing the modulation of outer bank erosion by slump blocks: A case study from Marqu Meadow, China - Lei Liu; Lekui Zhu; Dong Chen; Qihua Ran; Honglei Tang; Jun Yan; Lin Liu (Geomorphology, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Hydrogen peroxide enhanced Cu(II)/peroxymonosulfate system for naproxen degradation in natural water matrix and simultaneously reduced the formation potential of halogenated by-products - Jianying Wu; Jing Zou; Sheng Li; Chenyu Tang; Zhijie Wu; Linfeng He; Jinbin Lin; Qingsong Li; Jun Ma (Chemical Engineering Journal, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

Numerical Study of Hydrodynamic Characteristics of a Three-Dimensional Oscillating Water Column Wave-Power Device - Jun-Lin Zhu; Peng Tang; Hong-Sheng Zhang; Peng-Bo Zheng (Journal of Marine Science and Engineering, 2024)
The impact of wave-induced forces on the integrity of stationary oscillating water column (OWC) devices is essential for ensuring their structural safety. In our study, we built a three-dimensional numerical model of an OWC device using the computational fluid dynamics (CFDs) software OpenFOAM-v1912. Subsequently, the hydrodynamic performance of the numerical model is comprehensively validated. Finally, the hydrodynamic performance data are analyzed in detail to obtain meaningful conclusions. Results indicate that the horizontal wave force applied to the OWC device is approximately 6.6 to 7.9 times greater than the vertical wave force, whereas the lateral wave force is relatively small. Both the horizontal and vertical wave forces decrease as the relative water depth increases under a constant wave period and height. In addition, the highest dynamic water pressure is observed at the interface between the water surface and device, both within and outside the front wall of the gas chamber. The dynamic water pressure at different locations on the front chamber increases and subsequently decreases as the wave frequency increases.

Concentrations and influencing factors of 17 elements in placenta, cord blood, and maternal blood of women from an e-waste recycling area - Yacui Luo; Haijun Zhang; Fangzhong Gui; Jiayang Fang; Haijiang Lin; Danhong Qiu; Lingfei Ge; Qiong Wang; Peiwei Xu; Jun Tang (Journal of Trace Elements in Medicine and Biology, 2024)

Multiphysics and multi-scale design and analysis of nuclear thermal propulsion pellet bed reactor based on spherical cermet fuel element - Linyuan Lu; Shiqi Sun; Bin Tang; Guoqiang Wang; Ye Dai; Yajuan Zhong; Jun Lin (Annals of Nuclear Energy, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Association Between Prenatal Per- and Polyfluoroalkyl Substance Exposure and Maternal Serum Total Bile Acid Levels During Pregnancy: Effect Modification by Infant Sex and Maternal Prepregnancy BMI - Qian Liao; Huishen Huang; Peng Tang; Jun Liang; Jiehua Chen; Lei Lei; Yanye Song; Dongxiang Pan; Mengrui Lin; Fangfang Lv; Xue Liang; Xiaoyun Zeng; et al. (Exposure and Health, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

A vertical-flow constructed wetland–microalgal membrane photobioreactor integrated system for treating high-pollution-load marine aquaculture wastewater: A lab-scale study - Lin Zhao; Jun Tang; Yuwei Xu; Yifan Zhang; Zihao Song; Guiping Fu; Zhangli Hu (Science of The Total Environment, 2024)

4,5-Difluoro-1,3-dioxolan-2-one as a film-forming additive improves the cycling and thermal stability of SiO/C anode Li-ion batteries - Yong-Qi Wang; Lin-Jie Xie; Hui-Qi Sun; Xiang Wang; Hai-Lin Zhou; Yan Tang; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Transcriptome analysis reveals dysfunction of the endoplasmic reticulum protein processing in the sonic muscle of small yellow croaker (Larimichthys polyactis) following noise exposure - Xuguang Zhang; Xianming Tang; Jianan Xu; Yueping Zheng; Jun Lin; Huafeng Zou (Marine Environmental Research, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

The anti-cancer drug candidate CBL0137 induced necroptosis via forming left-handed Z-DNA and its binding protein ZBP1 in liver cells - Jun Li; Miao Tang; Ruo-Xian Ke; Pei-Lin Li; Zhi-Guo Sheng; Ben-Zhan Zhu (Toxicology and Applied Pharmacology, 2024)

Insights into the formation of halonitromethanes from dimethylamine involving bromide ion during UV/chloramine disinfection - Zhangjin Cao; Qian Tang; Lin Deng; Qing Wang; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2024)

Core taxa, co-occurrence pattern, diversity, and metabolic pathways contributing to robust anaerobic biodegradation of chlorophenol - Ming Lin; Chenhui Pan; Chenyi Qian; Fei Tang; Siwen Zhao; Jun Guo; Yongming Zhang; Jiaxiu Song; Bruce E. Rittmann (Environmental Research, 2024)

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Formation of halonitromethanes from glycine during LED-UV265/chlorine disinfection - Qian Tang; Liangwen Zhu; Qing Wang; Lin Deng; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Construction of molecular enrichment accelerators via assembly of enzyme surface grafted polymer and cyclodextrin achieving rapid and stable ester catalysis for biodiesel synthesis - Qi Ao; Lin Jiang; Xinglai Tong; Ying Song; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

The growth inhibitory effects and non-targeted metabolomic profiling of Microcystis aeruginosa treated by Scenedesmus sp - Xiao-lin Zhang; Qian-qian Zhu; Chuan-yue Chen; Bing Xie; Bin-guo Tang; Mei-hua Fan; Qun-ju Hu; Zhi Liao; Xiao-jun Yan (Chemosphere, 2023)

Dietary selenium promoted muscle growth (myofiber hypertrophy rather than hyperplasia) by reducing endoplasmic reticulum stress in juvenile grass carp (Ctenopharyngodon idella) - Ya Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Jun Jiang; Jia-Yong Tang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Multi-technological integration in a smelting site: Visualizing pollution characteristics and migration pattern - Lu Tang; Wenwan Chen; Xinghua Luo; Gubin Zhang; Xiang Feng; Lin Guo; Wenyan Gao; Jin He; Guizhang Zhao; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

A highly sensitive self-powered sensing method designed on DNA circuit strategy and MoS2 hollow nanorods for detection of thalassemia - Jinyue Shi; Danyao Tang; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

Corrigendum to “Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China” [Chemosphere. Dec 2022 309:136798] - Qian Liao; Peng Tang; Dongxiang Pan; Yanye Song; Lei Lei; Jun Liang; Bihu Liu; Mengrui Lin; Huishen Huang; Meile Mo; Chengtuo Huang; Ming Wei; et al. (Chemosphere, 2023)

Scour effects on the vertical dynamic response of single piles in transversely isotropic soils - Chun Lin Liu; Zhi Yong Ai; Meng Xiong Tang; He Song Hu; Lu Jun Wang (Ocean Engineering, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Far-field Coupling and Interactions in Multiple Geospheres After the Tonga Volcano Eruptions - Chieh-Hung Chen; Yang-Yi Sun; Xuemin Zhang; Fei Wang; Kai Lin; Yongxin Gao; Chi-Chia Tang; Jun Lyu; Rong Huang; Qian Huang (Surveys in Geophysics, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Application of a new basalt fiber-reinforced polymer anchorage structure in the tunnel—slope system under rainfall action - Lin Tang; Hong-gang Wu; Hong Wei; Kang Feng; Guo-jun Reng (Journal of Mountain Science, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Advancing charge carriers separation and transformation by nitrogen self-doped hollow nanotubes g-C3N4 for enhancing photocatalytic degradation of organic pollutants - Xinlan Zhen; Changzheng Fan; Lin Tang; Jun Luo; Linrui Zhong; Yuying Gao; Mingjuan Zhang; Jangfu Zheng (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Wind erodibility indices of aeolian sandy soils impacted by different vegetation restoration: a case study from the Shannan valley of the Yarlung Zangbo River - Bao-jun Zhang; Dong-hong Xiong; Lin Liu; Yong-fa Tang (Journal of Mountain Science, 2022)

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Links between continental subduction and generation of Cenozoic potassic–ultrapotassic rocks revealed by olivine oxygen isotopes: A case study from NW Tibet - Gong-Jian Tang; Derek A. Wyman; Qiang Wang; Lin Ma; Wei Dan; Ya-Nan Yang; Xi-Jun Liu; Hong-Yi Chen (Contributions to Mineralogy and Petrology, 2022)

Environmental consequences of an ultra-low emission retrofit in coal-fired power plants from a life cycle perspective - Jun Dong; Yuanjun Tang; Aizhong Ruan; Jie Chen; Xiaoqing Lin; Shengyong Lu; Xiang Gao (Waste Disposal & Sustainable Energy, 2021)

Associations of bisphenol exposure with the risk of gestational diabetes mellitus: a nested case–control study in Guangxi, China - Peng Tang; Jun Liang; Qian Liao; Huishen Huang; Xiaojing Guo; Mengrui Lin; Bihu Liu; Bincai Wei; Xiaoyun Zeng; Shun Liu; Dongping Huang; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2021)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

A combined semi-analytical algorithm for retrieving total suspended sediment concentration from multiple missions: a case study of the China Eastern Coastal Zone - Zhongli Liu; Jun Chen; Tingwei Cui; Junwu Tang; Lin Wang (International Journal of Remote Sensing, 2021)

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Biochar improves heavy metal passivation during wet anaerobic digestion of pig manure - Jun Wang; Xiaoxia Hao; Zile Liu; Zili Guo; Li Zhu; Bangjie Xiong; Dongmei Jiang; Linyuan Shen; Mingzhou Li; Bo Kang; Guoqing Tang; Lin Bai (Environmental Science and Pollution Research, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

High dietary lipid level alters the growth, hepatic metabolism enzyme, and anti-oxidative capacity in juvenile largemouth bass Micropterus salmoides - Yue-Lang Zhou; Jia-Ling Guo; Ren-Jun Tang; Hui-Jia Ma; Yong-Jun Chen; Shi-Mei Lin (Fish Physiology and Biochemistry, 2020)

A novel sunshine duration–based photothermal time model interprets the photosensitivity of flower maturity of pecan cultivars - Hua-Lin Ye; Qun-Ying Jin; Hua-Zheng Peng; Tang-Jun Zhu; Jian-Jun Shen; Guo-Shuai Huang; Min Wang (International Journal of Biometeorology, 2020)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Evaluation of the impact of karst depression-type impoundments on the underlying karst water systems in the Gejiu mining district, southern Yunnan, China - Hai-Yan Gao; Ze-Min Xu; Kun Wang; Zhe Ren; Kui Yang; Yong-Jun Tang; Lin Tian; Ji-Pu Chen (Bulletin of Engineering Geology and the Environment, 2019)

Pseudoxanthomonas composti sp. nov., isolated from compost - Jun Lin; Guiqin Yang; Jia Tang; Zhen Li; Zhen Yu; Li Zhuang (Antonie van Leeuwenhoek, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Impacts of small woody debris on slurrying, persistence, and propagation in a low-gradient channel of the Dongyuege debris flow in Nu River, Southwest China - Yong-Jun Tang; Ze-Min Xu; Tai-Qiang Yang; Zhen-Hua Zhou; Kun Wang; Zhe Ren; Kui Yang; Lin Tian (Landslides, 2018)

Hypoxic culture enhances the expansion of rat bone marrow-derived mesenchymal stem cells via the regulatory pathways of cell division and apoptosis - Jun Zhang; Lei Xiong; Wenxian Tang; Lin Tang; Baohe Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Geochronology, geochemistry, Sr–Nd–Hf isotopic compositions, and petrogenetic and tectonic implications of Early Cretaceous intrusions associated with the Duolong porphyry–epithermal Cu–Au deposit, central Tibet - Shaogang Wei; Yang Song; Juxing Tang; Zhibo Liu; Qin Wang; Bin Lin; Jun Feng; Lin Hou; Wangxiu Danzhen (International Geology Review, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Variations in cadmium and nitrate co-accumulation among water spinach genotypes and implications for screening safe genotypes for human consumption - Lin Tang; Wei-jun Luo; Zhen-li He; Hanumanth Kumar Gurajala; Yasir Hamid; Kiran Yasmin Khan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2018)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Identification and expression patterns of 20-hydroxyecdysone-responsive genes from Procambarus clarkii - Bao-Jian Zhu; Lin Tang; Ying-Ying Yu; Dao-Jun Wang; Chao-Liang Liu (Genes & Genomics, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Minocycline Attenuates Neonatal Germinal-Matrix-Hemorrhage-Induced Neuroinflammation and Brain Edema by Activating Cannabinoid Receptor 2 - Jun Tang; Qianwei Chen; Jing Guo; Liming Yang; Yihao Tao; Lin Li; Hongping Miao; Hua Feng; Zhi Chen; Gang Zhu (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

A Cannabinoid Receptor 2 Agonist Prevents Thrombin-Induced Blood–Brain Barrier Damage via the Inhibition of Microglial Activation and Matrix Metalloproteinase Expression in Rats - Lin Li; Yihao Tao; Jun Tang; Qianwei Chen; Yang Yang; Zhou Feng; Yujie Chen; Liming Yang; Yunfeng Yang; Gang Zhu; Hua Feng; Zhi Chen (Translational Stroke Research, 2015)

Mechanism of Developmental Stagnancy of Rice Inferior Spikelets at Early Grain-Filling Stage as Revealed by Proteomic Analysis - Zhixing Zhang; Jun Tang; Tingwei Du; Hong Zhao; Zhong Li; Zhou Li; Wenxiong Lin (Plant Molecular Biology Reporter, 2015)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

The Longmala and Mengya’a skarn Pb–Zn deposits, Gangdese region, Tibet: evidence from U–Pb and Re–Os geochronology for formation during early India–Asia collision - Liqiang Wang; Juxing Tang; Jun Deng; Haoran Kang; Xin Lin; Wenbin Cheng; Zhuang Li; Zhi Zhang (International Geology Review, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Chronic Hydrocephalus and Perihematomal Tissue Injury Developed in a Rat Model of Intracerebral Hemorrhage with Ventricular Extension - Qianwei Chen; Jianbo Zhang; Jing Guo; Jun Tang; Yihao Tao; Lin Li; Hua Feng; Zhi Chen (Translational Stroke Research, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Effect of high temperature on survival, oxygen consumption, behavior, ammonia-N excretion, and related immune indicators of the Japanese scallop Mizuhopecten yessoensis - Zhen-Lin Hao; Xue-Jiao Tang; Jun Ding; Yue Ben; Ya-Qing Chang (Aquaculture International, 2014)

Genome-Wide Fractionation and Identification of WRKY Transcription Factors in Chinese Cabbage (Brassica rapa ssp. pekinensis) Reveals Collinearity and Their Expression Patterns Under Abiotic and Biotic Stresses - Jun Tang; Feng Wang; Xi-Lin Hou; Zhen Wang; Zhi-Nan Huang (Plant Molecular Biology Reporter, 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken - Lin Jun Yan; Xing Tang Fang; Yao Liu; Chun Lei Zhang; Xuan Xuan Liu; Jing Zhao; Jing Jing Li; Hong Chen (Molecular Biology Reports, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

CXCR4 positive cells from Lewis lung carcinoma cell line have cancer metastatic stem cell characteristics - Wei-Qi Nian; Fang-Lin Chen; Xu-Jun Ao; Zheng-Tang Chen (Molecular and Cellular Biochemistry, 2011)

Cross-talk between NMDA and GABAA receptors in cultured neurons of the rat inferior colliculus - DanNi Cong; ZhengQuan Tang; LongZhu Li; YiNa Huang; Jun Wang; Lin Chen (Science China Life Sciences, 2011)

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Danshen protects endothelial progenitor cells from oxidized low-density lipoprotein induced impairment - Kang-ting Ji; Jun-de Chai; Cheng Xing; Jin-liang Nan; Peng-lin Yang; Ji-fei Tang (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

CIB1 and CaBP1 bind to the myo1c regulatory domain - Nanyun Tang; Tianming Lin; Jun Yang; J. Kevin Foskett; E. Michael Ostap (Journal of Muscle Research and Cell Motility, 2007)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

The solution structure of rat Aβ-(1–28) and its interaction with zinc ion: insights into the scarcity of amyloid deposition in aged rat brain - Jin Huang; Yong Yao; Jun Lin; Yong-Hao Ye; Wei-Yin Sun; Wen-Xia Tang† (JBIC Journal of Biological Inorganic Chemistry, 2004)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)